Egzorcyzm w Apokryfie Księgi Rodzaju (1Q20ar) na tle demonologii Starego i Nowego Testamentu - Kardyś, Wojciech (The Biblical Annals, 2024)
In the Genesis Apocryphon (1Q20ar), there is a story containing a description of an exorcism (col. 20). In that text, Abraham is asked to free Pharaoh who is plagued by a “spirit of pestilence”. By becoming an exorcist, the patriarch causes the demon to be banished. The aim of the article is to show this story against the background of biblical demonological texts. After presenting the figure of the evil spirit and its activity in 1Q20ar, the issue of the presence of demons in the Holy Scriptures is discussed (the evil spirit that harms Pharaoh most resembles the “lying spirit” from 1 Kings 22:19–22 and Satan from the Book of Job). The course of exorcism in the apocryphon and the means used by Abraham are also described, followed by a review of exorcisms in the Old and New Testaments. It turns out that the story about the expulsion of the demon in 1Q20ar differs from the one found in the Book of Tobit and in the descriptions present in the Gospels. In recapitulation, the conclusion is reached that despite some similarities in this field, the story in 1Q20ar retains its original and incomparable character. Perhaps it is a form of bridge between the “restrained” demonology of the Old Testament and the more developed doctrine of evil spirits in the New Testament.